2015
DOI: 10.1093/icc/dtv007
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing and firm performance: evidence from German firm data

Abstract: This paper uses a unique dataset to study the short term effects of downsizing on operational and financial performance of large German firms. In general, productivity and profitability after downsizing are -at the best -comparable to their pre-downsizing levels. During the downsizing event, the performance even drops. Moreover we make a distinction between firms downsizing because of a business downturn and firms downsizing to increase efficiency. Especially downsizing for the latter firms appears to be unsuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Habel and Klarmann (2015) assert that organisational employee reduction is correlated to decline in customer satisfaction especially in labour intensive organisations. An additional short fall pointed out by scholars is the fact that for layoffs to improve efficiency, it must be misunderstood by employees and this results in shattered employee (Goesaert et al, 2015;Rehman and Naeem, 2012). Richter and Konig (2017) assert that the method of labour force reduction through layoffs boils down to the employer's perception of fairness and labour legislation strictness and has no significant effect on the performance of an organisation.…”
Section: Labour Force Reduction Methods Implementedmentioning
confidence: 99%
See 3 more Smart Citations
“…Habel and Klarmann (2015) assert that organisational employee reduction is correlated to decline in customer satisfaction especially in labour intensive organisations. An additional short fall pointed out by scholars is the fact that for layoffs to improve efficiency, it must be misunderstood by employees and this results in shattered employee (Goesaert et al, 2015;Rehman and Naeem, 2012). Richter and Konig (2017) assert that the method of labour force reduction through layoffs boils down to the employer's perception of fairness and labour legislation strictness and has no significant effect on the performance of an organisation.…”
Section: Labour Force Reduction Methods Implementedmentioning
confidence: 99%
“…Although restructuring through delayering reduces payroll costs, the cost savings enjoyed are mitigated by the lower productivity of the demoted employees (Fraher, 2013 andGoesaert, Heinz andVanormelingen, 2015). The success of an organisation after restructuring activities such as delayering can prove to be disruptive to the normal pattern of doing things.…”
Section: Furloughs (Unpaid Leave)mentioning
confidence: 99%
See 2 more Smart Citations
“…Performance presented the operation results of participants that performance should be evaluated before performance management. Goesaert, Heinz, & Vanormelingen (2015) considered that performance evaluation was similar to physical examination of an organization to evaluate the quality of the organization and the goal achievement for fi nding out problems earlier and adopting coping measures.Theperformance evaluation results were also the benefi cial reference for an organization engaging in operation activity and resource allocation as well as revising management strategies and planning future directions. Lin et al (2017) concluded that the more intensivehuman capital of an enterprise, the high value-addedwork would be higher so that the employees could not be replaced.…”
Section: Organizational Innovationmentioning
confidence: 99%